2019
DOI: 10.1186/s13568-019-0800-y
|View full text |Cite
|
Sign up to set email alerts
|

Variations in phyllosphere microbial community along with the development of angular leaf-spot of cucumber

Abstract: The phyllosphere is colonized by a wide variety of microorganisms including epiphytes, plant-pathogenic fungus, bacteria, as well as human or animal pathogens. However, little is known about how microbial community composition changes with the development of angular leaf-spot of cucumber. Here, 18 mixed samples were collected based on the lesion coverage rate (LCR) of angular leaf-spot of cucumber from three disease severity groups (DM1: symptomatic-mild, DM2: symptomatic-moderate, DM3: symptomatic-severe). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 66 publications
3
33
0
Order By: Relevance
“…Generally, higher community complexity in a network reflects a more stable community structure ( Mougi and Kondoh, 2012 ). Stable microbial communities or consortia have greater ability to resist perturbation ( Ives et al , 2000 ; Luo et al , 2019 ; Morella et al , 2020 ). Studies using culture-independent DNA sequencing revealed similar microbial community patterns in successive year samplings ( Copeland et al.…”
Section: Role Of the Plant Immune System In Shaping The Leaf Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…Generally, higher community complexity in a network reflects a more stable community structure ( Mougi and Kondoh, 2012 ). Stable microbial communities or consortia have greater ability to resist perturbation ( Ives et al , 2000 ; Luo et al , 2019 ; Morella et al , 2020 ). Studies using culture-independent DNA sequencing revealed similar microbial community patterns in successive year samplings ( Copeland et al.…”
Section: Role Of the Plant Immune System In Shaping The Leaf Microbiomementioning
confidence: 99%
“…Much less is known about the dynamics and stability of leaf microbiomes in the field since there is a lack of high-resolution experimental data linked to plant disease and health with respect to time, space, and environmental scale. In recent studies, leaf diseases were linked to disruption of microbial community network stability, resulting in ecosystem dysfunction ( Kerdraon et al , 2019 ; Luo et al , 2019 ; Leopold and Busby, 2020 , Preprint). Understanding how a microbial community corrects itself under conditions of environmental stress is crucial to harness its potential in probiotic applications against aggressive plant pathogens and to track plant-associated human pathogen outbreaks.…”
Section: Role Of the Plant Immune System In Shaping The Leaf Microbiomementioning
confidence: 99%
“…Many studies have examined the correlation between the microbiome and plant disease, showing that the microbiome could be disease suppressive or conducive (Luo et al, 2019;Raza et al, 2019). OTU (Operational Taxonomic Units) biodiversity analysis of phyllosphere microbiome has been reported for during several tobacco diseases, including black shank, brown spot and pole rot of tobacco (Chen et al, 2019;Xiang et al, 2019;Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, they have been shown to dominate the endosphere of Origanum vulgare plants (Pontonio et al, 2018) and have been correlated negatively with disease symptoms of leaf spot on cucumber plants, presumably caused by P. syringae pv. lachrymans (Luo et al, 2019). Next to the production of hydrolytic enzymes by the biocontrol agents themselves, microbes can induce the production of chitinases in the host plant, a common defense reaction in plants.…”
Section: Hydrolytic Enzymesmentioning
confidence: 99%